PENGARUH MODEL PEMBELAJARAN TGT (TEAMS GAMES TOURNAMENT) BERBANTUAN MEDIA TTS (TEKA-TEKI SILANG) TERHADAP HASIL BELAJAR ASPEK KOGNITIF PEMBELAJARAN IPAS SISWA KELAS V SDN 5 SINGKAWANG - Agusriani; Emi Sulistri; Wasis Suprapto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine whether there are differences and influences in using the TGT (Teams Games Tournament) learning model assisted by TTS (Crossword Puzzle) media on the science and science learning of class V students at SDN 5 Singkawang as well as students' responses to the TGT learning model. The research used is quantitative research with a Quasi Experimental Design in the form of Pretest-Posttest Control Group Design. The population in this study were fifth grade students at SDN 5 Singkawang. This research sample uses samples based on class or also called Cluster Sampling. The data collection technique used in this research is a test technique in the form of learning outcomes in the cognitive domain and non-tests in the form of student response questionnaires. The data analysis technique used is quantitative analysis in the form of t-test, effect size and descriptive percentage. The results of the research show that: 1) There are differences in the cognitive learning outcomes of students who use the TGT (Teams Games Tournament) learning model with direct learning in science and science learning for class V students. This is shown based on the results of the polled t-test test calculation variant > is 9.125 > 2.017. 2) The TGT (Teams Games Tournament) learning model assisted by TTS (Crossword Puzzle) media in learning has a high influence on the cognitive learning outcomes of science and science subjects for class V students at SDN 5 Singkawang. This can be seen from the calculation of the effect size, namely 2.4944 and the criteria are high because 2.4944 is at ES > 0.8. 3) Positive student response to the TGT (Teams Games Tournament) learning model assisted by TTS (Crossword Puzzle) media in class V elementary school. This is shown from the calculations that the percentage of student responses of 84% is included in the high category.